Innovative composite wall designs for evaporatively cooled structures for storage of perishables - CHOPRA, SANGEETA; BEAUDRY, RANDOLPH (The Indian Journal of Agricultural Sciences, 2018)
The thermal performance of prototype evaporatively cooled (EC) structures using novel wall materials like pervious concrete (PC) and mesh supported fabric (MSF) were compared to a traditional brick-sand-brick (BSB) design. Structures were constructed at the Indian Agricultural Research Institute, Delhi and instrumented with thermocouples on the floor, on inner and outer surfaces of the walls and roof and in a 100 kg mass of simulated produce. The composite walls, roof, and floor were of unique designs and were made of specialized materials unused till now in EC structures. The thermal transmittance of the wall materials varied widely. Compared to BSB, average product temperatures over 5 days in June were approximately 2.5°C lower in PC and 3.5°C lower in MSF structures. The low thermal mass of the composite walls of MSF structure (almost 1/60th that of BSB walls), made the MSF structure cooler at night as it could follow the â€˜coolerâ€™ night air. Cost estimates for labour and materials suggested that PC and MSF structures would be 40 to 60% cheaper to construct than BSB structures.